Synthesis and characterization of novel azo-bridged Zn(II) and Co(II) bisphthalocyanines - (:unkn) unknown (Society of Porphyrins and Phthalocyanines (SPP), 2006)
Metal phthalocyanines containing an unsymmetrically substituted nitro group were synthesized from 4-nitrophthalonitrile and the corresponding anhydrous metal salts (Co(OAc)2, Zn(OAc)2) by the method of statistically mixed condensation reactions. The new type of metallobisphthalocyanine compounds connected by a N=N bridge was prepared from the reactions of respective nitro compounds with sodium hydroxide (NaOH) and activated zinc powder in a mixture of methanol (MeOH) and tetrahydrofuran (THF). The structures of these compounds were characterized by using 1H NMR, IR, elemental analyses, UV-vis and magnetic circular dichroism spectroscopies. Copyright © 2006 Society of Porphyrins & Phthalocyanines.
Keywords: Azo bridge; Cobalt; Magnetic circular dichroism; Phthalocyanine